PENGEMBANGAN GAME EDUKASI “GPP (GAME PENGENALAN PECAHAN)” UNTUK MEMFASILITASI PEMBELAJARAN SISWA KELAS IV PADA MATERI PECAHAN - Rahmawati, Elisabeth Denny; Setyadi, Danang (Universitas Bhinneka PGRI, 2026)
This study aims to develop a learning medium in the form of an Android-based Fraction Introduction Game to help fourth-grade elementary school students understand the concept of fractions in an interactive and enjoyable way. The game consists of three levels, namely the introduction of simple fractions, matching fractions with visual representations, and fraction conversion. The research method applies a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) combined with Tessmer’s formative evaluation (self-evaluation, expert review, one-to-one evaluation, and small group evaluation). The research instruments included validation sheets and practicality questionnaires, while effectiveness was tested through pretest and posttest using a paired sample t-test. The validation results showed a validity score of 96% (highly feasible), while the practicality test reached 97% (highly practical). The effectiveness test revealed a significant improvement in the matching fractions aspect (average score increased from 4.92 to 6.70; p = 0.005) and fraction conversion (from 1.92 to 2.56; p = 0.006), although the improvement in recognizing fractions was not significant. The conclusion of this study indicates that the Fraction Introduction Game is feasible, practical, and effective as a mathematics learning medium, especially for fraction topics, and can enhance students’ motivation and understanding.